Characterization of Eucalyptus maidenii timber for structural application: Physical and mechanical properties at two moisture conditions - Nogueira, Marta Cristina de Jesus Albuquerque; De Araujo, Victor Almeida; Vasconcelos, Juliano Souza [UNESP]; da Cruz, José Nilton; Vasconcelos, Julio Cezar Souza; Prataviera, Fabio; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (Hrvatski Sumarski Institut (Croatian Forest Research), 2018)
Background and Purpose: Eucalypt is an important raw material source of several industrial purposes. However, some eucalypt essences are still underutilized, possibly due to the lack of more embracing information about their properties. In this way, Eucalyptus maidenii species has presented a wide potential, and its lumber utilization is somewhat interesting. Nevertheless, a complete determination of its physical and mechanical properties, as carried out in this paper, certainly could encourage its popularization in construction. Materials and Methods: Eucalyptus maidenii evaluation included two physical and fourteen mechanical parameters, regarding standard documents from Brazilian National Standards Organization (ABNT) and American Society of Testing Materials (ASTM). Thus, a simple comparison was established concerning the moisture content of wood samples, which were evaluated through two conditions: 30% as the initial level and a standard at 12%. All results were statistically evaluated by t-test. In sixteen parameters, 310 determinations were carried out. Results: Half of mechanical properties presented significant changes in their resistances with the analysed moisture reduction. Modulus of rupture in static bending and in perpendicular compression, modulus of elasticity in perpendicular compression, strength in tangential cleavage, shear stress, and perpendicular and parallel hardnesses increased their resistances when the moisture content was reduced from 30% to 12%, that is, from green to dried standard stable point. Bulk density was also changed in the evaluated condition, decreasing to a smaller value. Volumetric mass density, modulus of rupture in parallel compression and in parallel and perpendicular tensiles, as well as modulus of elasticity in static bending and in parallel compression and tensile, and tangential toughness did not show any alteration in their values with this studied condition. Conclusions: Lumber for civil construction needs to be suitable for efficient application, with air equilibrium, generally at 12% of moisture content as international normative documents require. As part of this, mechanical and physical properties/parameters were studied to characterize Eucalyptus maidenii wood regarding moisture content. The results obtained indicate the use of this essence from planted forests for structural purposes in construction.
Keywords: Cleavage; Hardness; Maiden's gum; Shear stress; Strength modulus; Toughness; Wood density